Relation Between BMO and A2 Weight Functions (The Nepali Mathematical Sciences Report, 2016)
In this paper, we relate Bounded Mean Oscillation (BMO) function and A2 weight function. We show that logarithm of any A2 function is a BMO function and every BMO function is equal to a constant multiple of the logarithm of an A2 weight function. Moreover, we show that logarithm of any Ap weight function for 1 < p < ∞ is a BMO function.